HYPOCELLULAR MYELODYSPLASTIC SYNDROME PRESENTING AS MEGALOBLASTIC ANEMIA - Ishtiaq, Osama; Zahid, Muhammad; Baqai, Haider; Umer, Muhammad; Shoaib, Atifa; Bashir, Kaukab (Journal of Ayub Medical College Abbottabad, 2002)
Myelodysplastic Syndromes (MDS) are a heterogenous group of clonal stem cell disorders which generally occur in older adults but may also affect children. The ineffective hematopoiesis which causes bone marrow failure is accompanied by peripheral blood cytopenia1. MDS are classified into 5 different morphologic categories according to French-American-British (FAB) classification1,2,3. Hypocellular Myelodysplasia is a less common variant of MDS, characterized by hypocellular marrow in which a small proportion of blasts may be seen usually with occasional blasts in the peripheral blood2. We have encountered a distinct young patient of hypocellular MDS presented as megaloblastic anemia and pancytopenia.